2008
DOI: 10.1007/s12220-008-9040-0
|View full text |Cite
|
Sign up to set email alerts
|

Peak Points for Pseudoconvex Domains: A Survey

Abstract: Let D be a domain in C n with smooth (that is, C ∞ ) boundary. If 0 ≤ α ≤ ∞ we denote by A α (D) the space of functions holomorphic on D and of class C α on D. We write A(D) for A 0 (D) and A ω (D) for the space of functions holomorphic on a neighborhood of D. We say that a point p ∈ ∂D is a peak point relative to D for A α (D) if there exists a function f ∈ A α (D) so that f (p) = 1 and |f | < 1 on D \ {p}. We call f a peak function. This condition is clearly equivalent to the existence of a strong support fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Result 2.1 (Lemma 4.2, [11]). Let P be a homogeneous, plurisubharmonic, nonpluriharmonic polynomial in C n , n ≥ 2.…”
Section: Statement Of Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Result 2.1 (Lemma 4.2, [11]). Let P be a homogeneous, plurisubharmonic, nonpluriharmonic polynomial in C n , n ≥ 2.…”
Section: Statement Of Resultsmentioning
confidence: 95%
“…, z n−1 ), centered at ζ, such that Ω V ζ = (w, z) ∈ V ζ : Re(w) + P 2k (z) + O(|z| 2k+1 , |wz|, |w| 2 ) < 0 , where P 2k is a plurisubharmonic polynomial in C n−1 that is homogeneous of degree 2k. The first result in C n , n ≥ 3, to address (*) is due to Noell [11]. He showed that if P 2k is plurisubharmonic and is not harmonic along any complex line through 0, then Ω can be bumped homogeneously to order 2k around 0 ∈ C n .…”
Section: Diederich and Fornaessmentioning
confidence: 99%
“…For results about peak sets for Lipschitz classes in Cn, see Ababou–Boumaaz [1], Saerens [53], Cascante [14], and Noell [42].…”
Section: Peak Sets For Aαmentioning
confidence: 99%
“…The following theorem by Rossi [, Theorem 4.4], also mentioned in Noell's survey [, Remark 2.4 (2)], gives a sufficient condition for the existence of peak functions. Theorem If D is an open subset of a Stein manifold and D¯ has a basis of strictly pseudoconvex domains, then every local peak point for Aωfalse(Dfalse) is a global peak point for Aωfalse(Dfalse).…”
Section: Preliminariesmentioning
confidence: 99%